ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS MANAGEMENT PADA PERUSAHAAN MANUFAKTUR DI BEI - Budiman, Patricia Angelina; Susanti, Merry (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this research is to empirically examine the effect of profitability, leverage, firm size and sales growth on earnings management of manufacturing companies in the Indonesia Stock Exchange (IDX) for the period 2017-2020. The sampling technique used purposive sampling method and data processing using Eviews 9 SV software. In this research, there were 69 companies as samples from 276 companies and were analysed by multiple linear regression. The results of this research indicate that profitability has a positive and significant effect on earnings management, leverage and sales growth have a positive but not significant effect on earnings management, while firm size has a negative but not significant effect on earnings management.